1D Silver Nanowires/2D Graphene Composite Flexible Transparent Electrodes Induced by Superwetting Transfer - Xuanting Zhao; Yuqiang Zhang; Xingchao Chen; Chuao Ma; Chan Liu; Hongliang Liu; Shen Diao (Advanced Electronic Materials)
Abstract Silver nanowires (AgNWs) are promising materials for the fabrication of high‐performance flexible transparent electrodes (FTEs) due to their excellent optoelectronic properties, mechanical flexibility, and low‐cost solution processability. However, one serious obstacle that hinders the application of AgNWs‐based electrodes is the high contact resistance between AgNWs. Established methods for reducing contact resistance such as light‐induced welding, heat‐induced welding, and chemical welding require complex post‐treatment of the prepared AgNWs electrodes. Herein, a fully solution‐processable strategy is reported based on superwetting‐induced transfer for the preparation of composite FTEs electrodes without additional complex post‐process. The generated composite electrode is composed of 1D AgNWs as the percolation network and 2D graphene nanosheets as the conductivity‐enhanced component, significantly reducing the sheet resistance of the AgNWs film from 80.6 to 27.1 Ω·sq−1 while maintaining optical transmittance as high as 89.0%. The composite electrodes also exhibit superior mechanical bending stability and chemical stability. The composite electrodes are successfully applied to transparent heating devices, which show favorable thermal stability and heating effect. This study provides a new manner for the preparation of high‐performance FTEs, which can be compatible with large‐area and continuous production.